Mapping the effect of variable HPT blade cooling on fuel burn, engine life and emissions for fleet optimization using active control - Pontika, Evangelia; Laskaridis, Panagiotis; Montana Gonzalez, Felipe; Jacobs, Will; Mills, Andrew (American Institute of Aeronautics and Astronautics (AIAA), 2023)
Modern aero engines have increasingly sophisticated control systems. The aim for next-generation aircraft is to have even more adaptive and flexible control systems to enable the optimization of economic aspects, operational aspects and fleet management. Among others, an engine control variable that has the potential to offer various life and fuel burn benefits at different flight phases is the High-Pressure Turbine (HPT) blade cooling air. The HPT blades have demanding cooling requirements to protect their life and decelerate HPT efficiency degradation. However, any engine bleed has a penalty in efficiency and results in increased fuel consumption. Previous generation aircraft have a fixed relative blade cooling flow based on a design choice for a trade-off between life and efficiency. However, with adaptive control systems, there is an opportunity to extract the maximum potential benefit under different flight phases and scenarios. With this opportunity comes the challenge of increased complexity in engine behavior necessitating detailed modeling to quantify effects on lifing, fuel burn and safety. This paper focuses on modeling the performance, lifing and emission effects of variable HPT blade cooling air at take-off, climb and cruise. First, the effect of variable cooling on the Turbine Entry Temperature (TET), Exhaust Gas Temperature (EGT), fuel flow, lifing and NOx emissions are modeled at operating point level while the thrust requirement is achieved. Subsequently, a Design of Experiment is performed at mission level with the relative cooling flow at take-off, climb and cruise as the independent variables to train surrogate, analytical models. The analytical models are applied in the probabilistic modeling of system failure rates under different cooling flows. Optimization of engine control variables, in this case, the HPT blade cooling, requires analytical expressions that can be used in objective functions. These analytical models will inform fleet optimizers and active control systems to facilitate the implementation of fleet decisions such as reducing direct operating costs (fuel cost, maintenance reserves, NOx taxation), meeting NOx requirements of airports and extending Time-on-Wing (TOW). The findings indicate that take-off offers an opportunity to protect HPT life with increased cooling, but caution should be exercised in regard to the damage increase at the downstream non-cooled hot gas path components. A decrease in cooling flow at cruise, which is less detrimental to engine life, can offer significant fuel savings and climb can be investigated for the optimum economic trade-off between life and fuel burn as a response to economic scenarios.